PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN DESA WISATA DI DESA TANJUNG KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR PROVINSI RIAU - Saputra, Adi; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Tanjung Village Koto Kampar Sub District Hulu Kampar District has been awarded God with interesting tourism resources to visit. Rural development is geared towards integrated and comprehensive development activities by tricking every component of the community in order to improve the development of each village. The purpose of this research is as follows: To know community participation in the development of tourism village in Tanjung Village Koto Kampar Hulu District, Kampar District, Riau Province, To know the tendency of community participation in development of tourist village in Tanjung Village Koto Kampar Hulu District, Kampar Regency, Riau Province. Research uses quantitative methods. The study took place in Tanjung Village Koto Kampar Hulu Subdistrict of Kampar District. The population of 5.205 people using the Slovin formula is the total sample of 104 people spread in VII hamlet. Sampling method with probability sampling. From 10 (ten) questions asked in the research, it is concluded that: Tanjung Village society Koto Kampar Hulu Subdistrict of Kampar Regency tends to agree Tanjung Village is used as a tourist village, tends to hesitate to have ideas / input in the development of Desa Tanjung as a tourist village, - invited to participate in a meeting about Tanjung Desa development planning as a tourist village, tended to disagree with the meeting about the development of Desa Tanjung as a tourist village, tends to disagree directly involved in the development of Tanjung Village as a tourist village, tends to agree to benefit after Cape Village is made tourist village, tends to agree there is a lack of facilities in the development of Tanjung Village as a tourist village, tends to disagree on the development of Tanjung Village as a tourist village in accordance with the results of the meeting, tending to hesitate to follow gotong royong in the development of Tanjung Village as a tourist village, The endorsement disagrees with the management of the tourist village in Tanjung Village. Key words: Participation, Tourist Village